B48 DNA repair pathways as a common genetic mechanism modulating the age at onset in polyglutamine diseases. (13th September 2016) - Bettencourt, Conceição; Moss, Davina Hensman; Flower, Michael; Wiethoff, Sarah; Brice, Alexis; Goizet, Cyril; Stevanin, Giovanni; Koutsis, Georgios; Karadima, Georgia; Panas, Marios; Yescas-Gómez, Petra; García-Velázquez, Lizbeth Esmeralda; et al.
Abstract : Background: Over 30 human diseases are caused by expansion of unstable microsatellite sequences. Nine of these are caused by expanded CAG tracts encoding polyglutamines in different genes. This subgroup of diseases, usually referred to as the polyglutamine diseases which include Huntington's disease (HD), several spinocerebellar ataxias (SCAs), and spinal and bulbar muscular atrophy, are amongst the commonest hereditary neurodegenerative diseases. Longer CAG repeat tracts are associated with earlier ages at onset (AAO), but this does not account for all the variance, suggesting the existence of additional modifying factors. DNA repair pathways have been recently associated with the HD motor AAO in a recent HD GWAS. We therefore aimed to confirm the association between HD motor AAO and DNA repair pathways; and to investigate whether these modifying effects of variants in DNA repair genes can be extended to other polyglutamine diseases. Methods: We collected an independent cohort of 1462 subjects with HD and polyglutamine SCAs, and genotyped SNPs selected from the most significant hits in the HD study. Results: In an overall analysis of DNA repair pathway, we found the most significant association with AAO when grouping all polyglutamine diseases (HD+SCAs, p = 1.43 × 10 −5 ). Significant associations were also found for HD (p = 0.00194), all SCAs (p = 0.00107), SCA2 (p = 0.0035), and SCA6 (p = 0.00162). Testing individual SNPs, we found significant associations for rs3512 in FAN1 with HD+SCAs (p = 1.52 × 10 −5 ) and all SCAs (p = 2.22 × 10 −4 ), and rs1805323 in PMS2 with HD+SCAs (p = 3.14 × 10 −5 ). All these associations follow the same direction as in the HD GWAS. Conclusions: We show that DNA repair genes significantly modify the AAO not only in HD, but also in polyglutamine SCAs. This suggests a common pathogenic mechanism for these diseases, which could operate through the observed somatic expansion of repeats. Manipulation of DNA repair pathways may offer novel therapeutic opportunities in multiple diseases.